1997
DOI: 10.1007/bf02362170
|View full text |Cite
|
Sign up to set email alerts
|

The Israeli criminal justice system in action—Is justice administered differentially?

Abstract: IsThis study focuses on two major junctures in the Israeli criminal justice system, the preadjudication stage and the trial stage. The data are gathered from records accumulated during the period 1980 through 1992. For each year between 1980 and 1992, a random sample of 3637 persons, who had their first police contact during that year, was drawn from the computerized central file at Israeli Police Headquarters. A total of 40,007 individuals, with a total of 97,000 records, constituted the study population. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Over the years, many Palestinians abandoned their homes and families to become refugees in adjacent Arab countries (Palumbo 1987). This legacy affected not only the way Palestinians perceived Israeli officials and policies, but also the way Israelis (formally and informally) perceived and treated the Palestinians who remained in their midst (Cohen 1989;Hasin 1997;Fishman & Rattner 1997;Rouhana & Ghanem 1998;Zureik 1979;Zureik, Mughrabi & Sacco 1993).…”
Section: Palestinian-arab Society In Israelmentioning
confidence: 99%
“…Over the years, many Palestinians abandoned their homes and families to become refugees in adjacent Arab countries (Palumbo 1987). This legacy affected not only the way Palestinians perceived Israeli officials and policies, but also the way Israelis (formally and informally) perceived and treated the Palestinians who remained in their midst (Cohen 1989;Hasin 1997;Fishman & Rattner 1997;Rouhana & Ghanem 1998;Zureik 1979;Zureik, Mughrabi & Sacco 1993).…”
Section: Palestinian-arab Society In Israelmentioning
confidence: 99%
“…Israeli Arabs account for roughly 20% of the Israeli population but are largely overrepresented in the country’s criminal justice statistics (Central Bureau of Statistics, 2010a; Cohen & Palmor, 1985; Hassin, 1986; Hassin & Kremnitzer, 1988; Korn, 2003; Sherer, 1991). Studies note that this group faces worse sentencing outcomes than the Jewish majority (Cohen & Palmor, 1985; Fishman & Rattner, 1997; Fishman & Soroka, 1980; Rahav et al, 2015; Sherer, 1991) and have generally poorer relations with law enforcement (Hasisi & Weitzer, 2007). Even more so than Black and White populations in the United States, “intergroup conflict between Israeli Jews and Arabs is rooted in strife and rivalry,” with ethnic discrimination, political tensions, and hostilities consistent throughout history (Devers et al, 2012, p. 248).…”
mentioning
confidence: 99%
“…Although the bias is not unambiguous and calls for additional research, it seems that Arab offenders are more likely to receive prison or suspended prison sentences than Jewish offenders are, and less likely to be put on probation (Cohen and Palmor, 1985;Hassin and Kremnitzer, 1988). A more recent study (Fishman and Rattner, 1997) has found that Arabs have a greater chance of being discriminated against as their cases move along in the criminal justice system. In all offence categories, Arabs have a higher chance of conviction than do Jews.…”
Section: Discussion and Summarymentioning
confidence: 99%